2014
DOI: 10.1371/journal.pone.0087488
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Induced Glucagon-Like Peptide 1 Secretion Is Deficient in Patients with Non-Alcoholic Fatty Liver Disease

Abstract: Background & AimsThe incretins glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) are gastrointestinal peptide hormones regulating postprandial insulin release from pancreatic β-cells. GLP-1 agonism is a treatment strategy in Type 2 diabetes and is evaluated in Non-alcoholic fatty liver disease (NAFLD). However, the role of incretins in its pathophysiology is insufficiently understood. Studies in mice suggest improvement of hepatic steatosis by GLP-1 agonism. We determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 44 publications
6
63
1
Order By: Relevance
“…This finding is consistent with patients with type 2 diabetes having reduced beta cell sensitivity to the incretin hormones . Previous studies found blunted GLP‐1 secretion in obese patients with NAFLD compared to controls . The discrepancy may partly reflect differences in the selection of the control group and the fact that we included obese individuals as controls.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is consistent with patients with type 2 diabetes having reduced beta cell sensitivity to the incretin hormones . Previous studies found blunted GLP‐1 secretion in obese patients with NAFLD compared to controls . The discrepancy may partly reflect differences in the selection of the control group and the fact that we included obese individuals as controls.…”
Section: Discussionsupporting
confidence: 88%
“…However, it was observed that low GLP-1 levels were associated with a delayed glucose-lowering effect but increased and prolonged insulin secretion in patients with CRA. Similar trends have been reported in patients with non-alcoholic fatty liver disease [31], which is known to be related to insulin resistance and obesity. This observation suggests that hyperinsulinemia is caused by factors other than GLP-1 stimulation in these patients with adenoma.…”
Section: Discussionsupporting
confidence: 83%
“…3D), observations which agree well with those in a previous report (4). GLP-1 secretion is decreased in NASH patients (6) and GLP-1 reportedly attenuates NASH development (38). In addition, a GLP-1 receptor agonist reportedly suppressed SREBP1c expressions in the liver (32), and GLP-1 treatment decreased liver inflammation (40).…”
Section: Discussionsupporting
confidence: 89%